Study of Symbolic Meaning in Tuban Traditional Art Sandur Ronggo Budoyo - Umazah, Aulina (International Journal of Culture and Art Studies, 2021)
Traditional theatrical performance art is a valuable cultural asset in every region. Various performances of modern art have eroded traditional art into blurred and even invisible. The current globalization makes the existence of traditional art lose its true symbolic meaning because artists or artists prefer to follow the market in the process of cultivation. The traditional art of Sandur that still survives by prioritizing grip and symbolic things is the art of Sandur Ronggo Budoyo hamlet, Randu Pokak village, Prunggahan Kulon district, and Semanding Tuban district. The author is interested in researching this because some aesthetic things are studied from the symbolic study of the art of Sandur Ronggo Budoyo. This research uses a qualitative method with a case study approach—descriptive data analysis techniques with data reduction stages, data presentation, and inference. The informants in this study were government, community leaders, traditional art practitioners, and Sandur artists.